Hasil Belajar IPA Berdasarkan Gaya Belajar Siswa - Tri Ambarwati Adawiyah; Aloisius Harso; Adrianus Nassar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the differences in science learning outcomes of class VIII students of SMP Negeri 1 Larantuka who have visual, auditory and kinesthetic learning styles for the 2019/2020 academic year. The samples in this study were class VIII I and VIII J SMP Negeri 1 Larantuka. The research method used is quantitative with data analysis techniques using One Way Anova. Student learning styles are measured using a questionnaire that has been tested for validity and reliability first. Meanwhile, the learning outcome variable used the documentation method. The results of the F test showed that the value of Fcount <Ftable is 0.198 <2.53 with a significance value of 0.821> 0.05. In conclusion, there is no significant difference in science learning outcomes between students who have visual, auditory and kinesthetic learning styles. Keywords: Learning Style; Science Learning Outcomes